Convergence, productivity and debt: The case of Hungary - Dániel Baksa; István Kónya (Hungarian Academy of Sciences, Institute of Economics, 2019)
We study the role of productivity convergence and financial conditions in the recent growth experience of Hungary. We build a stochastic, small-open economy growth model with productivity convergence, capital accumulation and external borrowing. Using empirically identified processes for productivity and the external interest premium, we simulate the effects of two unexpected, permanent changes on Hungarian growth. The first change is the sharp productivity slowdown starting in 2006, and the second is the tightening of external financial conditions starting in 2009. Simulating our model, we show that the empirically identified productivity and interest premium processes - along with the two unexpected permanent changes and regular i.i.d. productivity and interest premium innovations - capture the main medium-run dynamics of the Hungarian economy both before and after the global financial crisis. Running counterfactuals, we also find that the observed slowdown in GDP per capita growth was mostly driven by productivity, while the tightening of external financing conditions is important to understand investment behavior and the net foreign asset position.
Keywords: E13; E22; F43; O47; 330; economic growth; convergence; productivity; interest premium; Hungary